Pelafalan Fonem Oleh Penderita Disartria - Antono, Mixghan Norman (STKIP PGRI Ponorogo Press, 2025)
Problems with phoneme pronunciation disorders can occur if a person experiences disorders or abnormalities in the central nervous system or muscles involved in sound formation. In connection with the problem of phoneme pronunciation disorders, the problem that will be discussed in this study is the phenomenon of phoneme pronunciation disorders that occur in children aged 8 years, adolescents aged 23 years and adults aged 56 years with dysarthria in Pragelan Village, Bojonegoro. The purpose of this study was to determine how the pronunciation of phonemes in children suffering from dysarthria in Pragelan Village, Bojonegoro. The method used in this research is descriptive qualitative with the method of listening. This study is a phonological study that aims to explain the form of phoneme pronunciation disorders pronounced by dysarthria sufferers. The study used two sources as data, by analyzing the utterances they uttered. From the results of the discussion, it was found that the phenomenon of impaired phoneme pronunciation in Pragelan Village, Bojonegoro, was the pronunciation of phonemes in dysarthria sufferers with symptoms of speaking too slowly, unable to speak at a loud volume, stroke and slurred.